Relationship of Knowledge and Attitude among Midwives with the Implementation of Early Initiation of Breastfeeding in Badung Regency - Luh Sudemi; Kadek Tresna Adhi; Dyah Pradnyaparamita Duarsa (Universitas Udayana, 2016)
Background and purpose: Infant Mortality Rate (IMR) in Bali and also in Indonesia is still high while the proportion of exclusive breastfeeding fully for six months is still very low. One effort to improve exclusive breastfeeding is the early initiation of breastfeeding (EIB) i.e. breastfeeding to infants shortly after birth. This study was conducted to determine the implementation of EIB by midwives and the factors that influence it. Methods: The study design was cross-sectional survey among 61 private practice midwives as respondents in Badung Regency. The respondents were all private practice midwives in three regencies purposively selected from six districts in Badung Regency. The data were collected through questionnaires filled out by midwives and analyzed by bivariate with chi-square test and multivariate using poisson regression method. Results: The EIB was implemented by 62.3% of the respondents. In the group of midwives having >4 patients per month significantly implemented the EIB more compared with those having ≤4 patients per month i.e. 83.3% and 57.1% respectively (p=0.008). The implementation of EIB had a significant difference among midwives with higher knowledge i.e. 84.6% and 45.7% respectively (p=0.002), midwives having positive attitude were 79.1% vs. 22.2% p<0.001 and those having received supervision, namely 77.5% vs. 33.3%(p=0.001). Multivariate analysis showed that factors associated with implementation of EIB were knowledge with APR=1.5 (95%CI: 1.04- 2.1) and attitude with APR=2.7 (95%CI: 1.1-6.3). Conclusion: Knowledge and attitude had a significant relationship to the implementation of EIB by midwives.